Who will re-fix the contest of baal and the true God?’: analysing the re-surging dibia practices in an African community - Paulinus Okechukwu Agbo (Humanities & Social Sciences Communications)
Abstract Rekindled passions and revival of indigenous beliefs and practices have become one of the emerging conversations on African Religions (AR). This paper draws upon an ethnographic study of the Nsukka-Igbo communities to negotiate the impetus for the increasing dibia (broadly defined as medicine man/priest/diviner/healer) practices among the Igbo of Nigeria. Despite the informed school of thought contemplating African Religions and their attendant agencies as being in retreat, evidence from this study portrays a rejuvenation of indigenous knowledge and practices dealing with health concerns particularly as found in dibia practices. As discovered, this new trajectory, among other constructs, is shaped by the youth’s reawakening trust in local knowledge systems. This account maps into the discourse on the resurgence of indigenous health agencies in the midst of the dominant Western medium of seeking wellness in postcolonial conditions.